National Personality in Maintaining the Honor and Nobility of Judges in Indonesia - Agus, Azwir; Meher, Montayana (Journal of Education, Humaniora and Social Sciences (JEHSS), 2025)
This study aims to analyze the legal regulations related to the Contempt of Court and Acts Degrading the Honor and Dignity of Judges (PMKH) in Indonesia. As a country based on law, Indonesia places Pancasila as the foundation for building a fair, dignified, and transparent justice system. The phenomena of Contempt of Court and PMKH are serious challenges in maintaining the integrity and independence of judicial institutions, which have a direct impact on public trust in the legal system. This study uses a library method with a descriptive qualitative approach, analyzing laws and regulations such as the Criminal Code, Criminal Procedure Code, and relevant legal literature. The results of the study show that although related regulations have been regulated in various regulations, proportional, fair, and transparent law enforcement is still needed. This effort is important to ensure that the supremacy of law is maintained, in line with the values of Pancasila as the personality of the Indonesian nation in supporting a dignified justice system.